2004
DOI: 10.1046/j.1365-2672.2004.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of EDTA/antimicrobial combinations on Pseudomonas aeruginosa

Abstract: Aims: To demonstrate that the nonlinear concentration-dependent inhibition of Pseudomonas aeruginosa to EDTA can be used to successfully model and predict the potentiation of antimicrobials by EDTA. Methods and Results: A model used successfully to describe the concentration-dependent inhibition of bacterial growth caused by many antimicrobials was unable to describe the inhibition of P. aeruginosa by EDTA. Examination of the inhibition profiles for EDTA against P. aeruginosa revealed a biphasic inhibitory pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
70
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 18 publications
4
70
3
2
Order By: Relevance
“…15 Earlier studies have shown that EDTA at 50 mM is useful in disrupting the biofilm. 16,17 Contrary to this, we noted that EDTA at 10 mM was found to be effective in disruption of bacterial biofilm when used alone. A large number of antibiotics and their combinations are available in the market.…”
contrasting
confidence: 66%
“…15 Earlier studies have shown that EDTA at 50 mM is useful in disrupting the biofilm. 16,17 Contrary to this, we noted that EDTA at 10 mM was found to be effective in disruption of bacterial biofilm when used alone. A large number of antibiotics and their combinations are available in the market.…”
contrasting
confidence: 66%
“…Although prolonged treatments with EDTA are lethal, short treatments increase the permeability of the outer membrane to hydrophobic molecules (25,29). Thus, there can be synergy between EDTA and other antibacterial agents (2,8,24). In this study we report that EDTA not only kills P. aeruginosa planktonic cells but also affects P. aeruginosa biofilms ( Fig.…”
Section: Discussionmentioning
confidence: 56%
“…EDTA, a preservative in the food, drug, and cosmetic industries (16,22,28,31,43,60), has been shown to potentiate the antibiotic activity of nanoemulsions containing CPC against Gram-positive and Gram-negative bacteria. Farca et al have shown the synergistic effect of EDTA with five antimicrobial agents, ampicillin, cephalexin, oxytetracycline, streptomycin, and sulfadimethoxine, on three clinically isolated Gram-positive bacteria (Staphylococcus aureus, Staphylococcus hominis, and Enterococcus faecium) even in the absence of nanoemulsion delivery (16).…”
Section: Discussionmentioning
confidence: 99%